PARADIGM SHIFT OF ISLAMIC EDUCATION POLICY IN INDONESIA - Ahsari Fadli Siregar; Faridi (As-Sulthan Journal of Education, 2026)
Islamic education in Indonesia has continuously evolved in response to socio-political change, governance reform, and technological disruption. This article examines the paradigm shift of Islamic education policy across three governmental eras: the Gotong Royong Cabinet, Indonesia Bersatu Cabinet, and Indonesia Maju Cabinet. The study aims to analyze the characteristics, continuity, and transformation of Islamic education paradigms within these periods and their implications for national educational quality. Employing qualitative descriptive research with a historical-comparative approach, data were collected through systematic library research of academic journals, scholarly books, and official policy documents published between 2001 and 2025. The data were analyzed using thematic analysis to identify patterns of policy orientation and paradigm transformation. The findings indicate that Islamic education policy has undergone a gradual transformation from a normative–traditional paradigm emphasizing moral reconstruction, to an integrative paradigm focusing on professionalization and system integration, and finally to an innovative–integrative paradigm characterized by religious moderation and digitalization. This evolution reflects the dynamic interaction between Islamic values, state policy, and global educational demands. The study contributes to the discourse on Islamic education reform by highlighting the importance of policy continuity, value-based modernization, and balanced integration of spirituality and technology in shaping sustainable Islamic education systems.